Social capital and education outcomes in urban and rural Peru - Cueto, S; Guerrero, G; Leon, J; De Silva, M; Huttly, S; Penny, M; Lanata, C; Villar, E (2005)
Although enrolment in primary schools in Peru is very high, more than half of primary school children are one or more grades below the norm for their age. Evaluations show Peruvian school children score well below the global average for their age and the average of countries with similar socio-economic circumstances. The role of social capital, or social networks and support, trust, and reciprocity, in explaining these findings has not been studied. Research in the United States has suggested positive associations between social capital and educational achievement. Young Lives researchers have examined whether social capital is associated with educational progress and achievement in Peru. In this paper, the authors consider the impact of social capital on children aged 7.5 to 8.5, focusing on whether or not the child is in a school grade corresponding to his/her age and achievements in mathematics and language. The findings in this paper confirm poor educational outcomes for many Peruvian school children. High proportions were unable to master simple tasks and were in a lower grade than they should have been considering their age. Educational achievement is clearly linked to poverty. Rural students are poorer and even more likely to achieve test results below their expected grade. This seems to be equally the case for both boys and girls. The results here do not support the hypothesis of a positive association between the social capital available to the family and their children’s educational attainment – but do show an association between cognitive social capital at the community level (norms, values, attitudes, and beliefs) and children being in the correct grade for their age. Communities in which there are relations of trust are more likely to have children who are in the correct school grade for their age. This finding applies to how children are progressing at school (whether they are in the correct grade for their age), but does not apply to their achievement (results in tests).